Effects of chlorogenic acid on carbachol-induced contraction of mouse urinary bladder - Takeharu Kaneda; Noriyasu Sasaki; Norimoto Urakawa; Kazumasa Shimizu (Elsevier, 2018)
Chlorogenic acid (CGA) is a polyphenol found in coffee and medicinal herbs such as Lonicera japonica. In this study, the effect of CGA-induced relaxation on carbachol (CCh)-induced contraction of mouse urinary bladder was investigated. CGA (30-300 μg/ml) inhibited CCh- or U46619-induced contraction in a concentration-dependent manner. SQ22536 (adenylyl cyclase inhibitor) recovered CGA-induced relaxation of CCh-induced contraction; however, ODQ (guanylyl cyclase inhibitor) did not have the same effect. In addition, 3-isobutyl-1-methylxanthine (IBMX) enhanced CGA-induced relaxation; however, forskolin or sodium nitroprusside did not have the same effect. Moreover, Ro 20-1724, a selective phosphodiesterase (PDE) 4 inhibitor, enhanced CGA-induced relaxation, but vardenafil, a selective PDE5 inhibitor, did not have the same effect. In the presence of CCh, CGA increased cyclic adenosine monophosphate (cAMP) level, whereas SQ22536 inhibited the increase of cAMP levels. Moreover, higher cAMP levels were obtained with CGA plus IBMX treatment than the total cAMP levels obtained with separate CGA and IBMX treatments. In conclusion, these results suggest that CGA inhibited CCh-induced contraction of mouse urinary bladder by partly increasing cAMP levels via adenylyl cyclase activation.